Influence of the psycho-pedagogical accompaniment program on the perception of happiness of university students - Díaz Díaz, Flor Del Rosario; Acosta Enriquez, Benicio Gonzalo; Yupanqui Pereda, Juan; Villena Zapata, Luigi Italo; López Roca, Carlos (LACCEI, 2023)
A psycho-pedagogical accompaniment program was carried out; with the intention of measuring its influence on the perception of happiness in students of the National University of Trujillo, with an age range between 17 and 21 years old. Methodologically, a quantitative approach was used, whose design was of experimental type, the data were collected using the Lima de Alarcon Happiness Scale[1]; four factors were examined: positive sense of life, satisfaction with life, personal fulfillment and joy of living, before and after the experience of psycho-pedagogical accompaniment, it was concluded that: (1) The program significantly influenced (p=0.0000953